A Project Report on Scalable Wireless AD-HOC Network Simulation using XTC Algoritham - BHARATH A, SHWETHA T, SNEHA PRADHAN and YAMINI S (2007)
INTERNAL GUIDE: SHREEKANTH V P, MVJCE EXTERNAL GUIDE:SHAIK JAVEED PROJECT CHIEF
Keywords: Scalable Wireless AD-HOC Network Simulation using XTC Algoritham